Globalization and Workers in Developing Countries - Rama, Martin (World Bank, Washington, DC, 2014)
Stories on the positive and negative effects of globalization on workers in developing countries abound. But a comprehensive picture is missing and many of the stories are ideologically charged. This paper reviews the academic literature on the subject, including several studies currently under way, and derives the implications for public policy. First, it deals with the effects of openness to trade, foreign direct investment, and financial crises on average wages. Second, it discusses the impact of exposure to world markets on the dispersion of wages by occupation, skill, and gender. Third, it describes the pattern of job destruction and job creation associated with globalization. Because these two processes are not synchronized, the fourth issue addressed is the impact on unemployment rates. Fifth, the paper reviews the labor market policies that can be used to offset the adverse effects of globalization on employment and labor earnings. Finally, it discusses how the international community could encourage developing countries to adopt sound labor market policies in the context of globalization.